(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
Technological developments continue to have an existential impact on the normative understanding of the community radio sector of South Africa. Advances, trends and changes in the technological sphere have meant that as researchers we need to keep up and re-think the long debated matter of “community” within the community radio sector. Within the discourse of continuing research,this re-thinking is being necessitated by the rapid introduction of new media and new forms of information and communication technologies (ICT) within the broadcasting space. In addition to these ICTs, the mandate and growth of some of the media institutions broadcasting as community radio stations in South Africa have changed – in some cases from small to regional broadcasters. In this paper, I examine the impact of ICTs as well as the accelerated growth of some community broadcasting institutions and their impact on the normative and conceptual understanding of the broadcasting sector. Using a case study perspective, the examination of such developments within the sector has been carried out through Vukani Community Radio (VCR) as a case study. This is one of the oldest community radio stations in South Africa. Drawing on theories about the decoloniality of knowledge, this paper argues that new trends that are emerging within the technological space, as well as community of reception dynamics, forces the academic, research and policy fraternity to re-look the conceptual understanding of the community radio sector of South Africa.